Accessibility and Digital Mental Health: Considerations for More Accessible and Equitable Mental Health Apps - Bunyi, John; Ringland, Kathryn E.; Schueller, Stephen M. (Frontiers in Digital Health, 2021)
Digital mental health is often touted as a solution to issues of access to mental health care. However, there has been little research done to understand the accessibility of digital mental health, especially for those with disabilities. In this piece, we define accessibility as it relates to mental health apps, describe the current state of accessibility in the digital world broadly and in mental health apps more specifically, outline why accessibility matters in mental health apps, and identify future steps to better incorporate accessibility into research and development of mental health apps.